Analysis of Ijarah Accounting Application Based on PSAK 107 at PT Pegadaian Syariah UPS Perjuangan, Cirebon - Komala Dewi (Journal of Management, Economic, and Financial, 2023)
Pegadaian Syariah is a state-owned enterprise in the form of a non-bank financial institution engaged in services. Sharia pawnshops have an important role in assisting the government by expanding equitable development, increasing income and community prosperity with poverty alleviation programs. This study was conducted to determine the application of ijarah accounting in gold pawn financing (Rahn) at PT Pegadaian Syariah UPS Perjuangan Cirebon City and to determine the suitability of the application of ijarah accounting in gold pawn financing (rahn) at PT Pegadaian Syariah UPS Perjuangan Cirebon City based on PSAK 107. Research This research uses qualitative research, data collected by interview, observation, documentation, and literature, then analyzed by descriptive analysis method. The results of this study indicate that the application of ijarah accounting in gold pawn financing (rahn) at PT Pegadaian Syariah UPS Perjuangan Cirebon City includes rahn financing requirements, mechanism for submitting and paying off rahn financing, contracts and costs associated with rahn financing, as well as calculating the ijarah fee. Ijarah calculation at PT Pegadaian Syariah UPS Perjuangan Cirebon City is calculated every 10 days within a time limit of 120 days or 4 months. The application of ijarah accounting in gold pawning financing (rahn) based on PSAK 107 at PT Pegadaian Syariah UPS Perjuangan Cirebon City regarding recognition and measurement is in accordance with PSAK 107, but the presentation is not fully in accordance with PSAK 107 because there are no reported repair costs for the ijarah object. to the uterus. It's just that there is an ijarah fee that is charged to rahin and PT Pegadaian Syariah UPS Perjuangan Cirebon City whose financial reports are carried out centrally and online so there are no special reports.